CIVIL SERVICE REFORM IN EU COUNTRIES - Nikolin AGALLİJA (Fırat University, 2019)
Many European countries have adopted laws or they are making draft laws on the civil service based on some unified principles. It has been widely recognized that no country can properly exercise its duties without a highly organized and stable civil service. However, the extent to which permanent civil service should operate still remains a controversial issue. The enforcement of a new reform on the civil service does not necessarily involve the passing of a legal act that would regulate the juridical relations in a completely new manner. Indeed, the reform is about introducing new attitudes to an existing legal domain, so that their implementation might bring innovation to the handling of certain issues that require solution. In EU countries there is an emergent need to reform the current civil service for practical or social reasons, which has been encouraged as something that would lead toward the unification of the civil service. The Public administration must be permanent so as to promote institutional and professional knowledge in order to resolve complex political issues that concern modern societies. As the main component of public administration, the staff is the reason why civil service extension is the key problem that requires solution. An important challenge is that of determining – for the purposes of a new civil service – the enforcement of government policies, the exercise of public authority and the management of public funds. Indeed, the entirety of EU principles and rules on the free circulation of employees, capitals, etc., would sound more complete and accomplished if it was implemented even in the framework of the civil service. It would have been an additional success if we consider that until recently civil service has been described as the opportunity of any country to regulate its functioning only in the framework of the national law. Therefore, this work is aimed at dealing with the process of civil service reform in EU countries, so that member and aspiring states might implement the same institutes for an optimal functioning of the civil service based on unified principles, which acquire the status of “acquis communitare”.